Investors' Expectations of Earnings Growth, Their Accuracy and Effects on the Structure of Realized Rates of Return - Ofer, Aharon R. (Journal of Finance, 1975)
Aharon R. Ofer, Investors' Expectations of Earnings Growth, Their Accuracy and Effects on the Structure of Realized Rates of Return, The Journal of Finance, Vol. 30, No. 2, Papers and Proceedings of the Thirty-Third Annual Meeting of the American Finance Association, San Francisco, California, December 28-30, 1974 (May, 1975), pp. 509-523